The identification and correction of pseudohypercalcemia - Yu, Tongyong; Li, Xiaozhe; Huang, Beihui; Gu, Jingli; Liu, Junru; Chen, Meilan; Li, Juan (Frontiers in Oncology, 2024)
BackgroundWe found that a subset of patients with monoclonal gammopathy exhibited hypercalcemia without apparent causes or clinical manifestations In a cohort of 289 monoclonal gammopathy patients, 2.4% presented with such atypical hypercalcemia, with one notable case exhibiting normal ionized calcium levels, suggesting the presence of pseudohypercalcemia.ObjectiveThe aim of this study is to elucidate the factors contributing to pseudohypercalcemia in monoclonal gammopathy and to develop a novel globulin-corrected calcium formula for clinical application.MethodsThis observational study enrolled 110 monoclonal gammopathy patients from our center. An additional 33 patients were recruited to validate the newly proposed formula. Univariate analysis identified potential risk factors. And multivariate logistic regression identified definitive influential factors. The determined influential factors were utilized to develop a formula by multiple linear regression, which was validated by a paired t-test and the Youden index.ResultsThis study found that globulin was a risk factor for pseudohypercalcemia. It revealed that pseudohypercalcemia should be considered in patients with globulin levels ≥61 g/L (P=0.014). Both albumin and globulin were confirmed as independent factors associated with bound calcium. Given that, we developed a formula to correct ionized calcium levels, which was consistent with ionized calcium tested by blood gas analysis. The diagnostic accuracy of the new formula (Youden index is 0.906) is better than the traditional formula (Youden index is 0.906). Interestingly, all monoclonal immunoglobulin types, except for light chains, showed an equal propensity to develop pseudohypercalcemia (P=0.306). It also showed a linear correlation between IgA, IgG, and IgM and bound calcium.ConclusionThis study confirmed that elevated globulin affects serum total calcium and offered the threshold of globulin ≥ 61 g/L in the differential diagnosis of peudohypercalcemia from hypercalcemia. The new formula based on albumin and globulin was developed, which was verified to be better than the traditional formula for correctly diagnosing hypercalcemia. In addition, we found that neither light chains nor heavy chains of monoclonal immunoglobulin alone can result in pseudohypercalcemia.